Association Between Left Ventricular Relative Wall Thickness and Acute Kidney Injury After Noncardiac Surgery. (25th April 2022) - Goeddel, Lee A.; Erlinger, Samuel; Murphy, Zachary; Tang, Olive; Bergmann, Jules; Moeller, Shaun; Hattab, Mohammad; Hebbar, Sachinand; Slowey, Charles; Esfandiary, Tina; Fine, Derek; Faraday, Nauder
Abstract : BACKGROUND: Acute kidney injury (AKI) after major noncardiac surgery is commonly attributed to cardiovascular dysfunction. Identifying novel associations between preoperative cardiovascular markers and kidney injury may guide risk stratification and perioperative intervention. Increased left ventricular relative wall thickness (RWT), routinely measured on echocardiography, is associated with myocardial dysfunction and long-term risk of heart failure in patients with preserved left ventricular ejection fraction (LVEF); however, its relationship to postoperative complications has not been studied. We evaluated the association between preoperative RWT and AKI in high-risk noncardiac surgical patients with preserved LVEF. METHODS: Patients ≥18 years of age having major noncardiac surgery (high-risk elective intra-abdominal or noncardiac intrathoracic surgery) between July 1, 2016, and June 30, 2018, who had transthoracic echocardiography in the previous 12 months were eligible. Patients with preoperative creatinine ≥2 mg/dL or reduced LVEF (<50%) were excluded. The association between RWT and AKI, defined as an increase in serum creatinine by 0.3 mg/dL from baseline within 48 hours or by 50% within 7 days after surgery, was assessed using multivariable logistic regression adjusted for preoperative covariates. An additional model adjusted for intraoperative covariates, which are strongly associated with AKI, especially hypotension. RWT was modeled continuously, associating the change in odds of AKI for each 0.1 increase in RWT. RESULTS: The study included 1041 patients (mean ± standard deviation [SD] age 62 ± 15 years; 59% female). A total of 145 subjects (13.9%) developed AKI within 7 days. For RWT quartiles 1 through 4, respectively, 20 of 262 (7.6%), 40 of 259 (15.4%), 39 of 263 (14.8%), and 46 of 257 (17.9%) developed AKI. Log-odds and proportion with AKI increased across the observed RWT values. After adjusting for confounders (demographics, American Society of Anesthesiologists [ASA] physical status, comorbidities, baseline creatinine, antihypertensive medications, and left ventricular mass index), each RWT increase of 0.1 was associated with an estimated 26% increased odds of developing AKI (odds ratio [OR]; 95% confidence interval [CI]) of 1.26 (1.09–1.46; P = .002). After adjusting for intraoperative covariates (length of surgery, presence of an arterial line, intraoperative hypotension, crystalloid administration, transfusion, and urine output), RWT remained independently associated with the odds of AKI (OR; 95% CI) of 1.28 (1.13–1.47; P = .001). Increased RWT was also independently associated with hospital length of stay and adjusted hazard ratio (HR [95% CI]) of 0.94 (0.89–0.99; P = .018). CONCLUSIONS: Left ventricular RWT is a novel cardiovascular factor associated with AKI within 7 days after high-risk noncardiac surgery among patients with preserved LVEF. Application of this commonly available measurement of risk stratification or perioperative intervention warrants further investigation.